The Evolution of Psychological and Emotional Effects of Visitation on Families of People Incarcerated in the United States - Trahan, Adam; Evans, Douglas N.; Voss, Andrew S. (International Journal of Criminology and Sociology, 2025)
Purpose: Recent research has explored the collateral effects of incarceration on families. This study extends this research by exploring the psychological and emotional effects of visitation on family members of people incarcerated. Design: Data come from in-depth interviews with 35 participants who experienced an immediate family member’s incarceration. Transcripts of these interviews were analyzed using reflexive thematic analysis. Findings: Results of a thematic content analysis show complex harms families suffer before, during, and after visitation and identify their sources. Findings further show how families became accustomed to a custodial environment and gradually draw on informal peer support networks developed over repeated visits to prison to mitigate the negative effects of visitation. Conclusions: Policy interventions should focus on enhancing connections between incarcerated persons and their families. Policies should also prioritize respect, privacy, and meaningful engagement during visitation. Additionally, standardizing and improving the communication of rules that visitors must follow, the processes they must traverse, and the correctional officers who manage both would mitigate the psychological and emotional suffering of family members. Finally, family reunification programs should begin during incarceration to prepare individuals to engage with their families in healthy ways prior to their release and return home.